Developing Multimodal PowerPoint Animations for Enhancing Students’ Reading Comprehension: A Research and Development Study - Aulia Lestari; Amalia Yahya; Yuyun Ruqiyyat Said (FOSTER: Journal of English Language Teaching, 2025)
This study aimed to develop an interactive English PowerPoint animation to improve junior high school students’ reading comprehension and to identify the most effective interactive features for reading instruction. Using a Research and Development (R&D) approach based on the 4D model, the study was limited to the define, design, and develop stages. The participants were one English teacher and 20 ninth-grade students at SMPN 7 Palopo. Data were collected through questionnaires, interviews, expert validation, and classroom try-outs. The results showed that the developed media was highly effective, achieving a mean score of 3.61 and an effectiveness rate of 90.25% (“Very Good”). Expert validation confirmed high feasibility in terms of content, language, design, and interactivity. Key features contributing to its effectiveness included animated text and images, interactive quizzes, educational games, vocabulary audio, and reading materials adapted from students’ textbooks. These features enhanced students’ engagement, motivation, and comprehension during reading activities. The novelty of this study lies in the integration of curriculum-aligned reading texts, multimodal animations, and game-based interactive elements within a single PowerPoint-based medium that functions fully offline. This design offers a practical and accessible solution for schools with limited internet access. The findings indicate that interactive PowerPoint animation can support more student-centered reading instruction and serve as an effective alternative to traditional textbook-based learning in EFL classrooms.